2005
DOI: 10.1017/s1431927605506901
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Beam Electron Diffraction of Ordered L10 Nanoparticles

Abstract: We have determined the long-range order parameter of individual [001] oriented FePt L1 0 nanoparticles. Measurement of convergent beam electron diffraction intensities of single particles in scanning transmission electron microscopy (STEM) mode, and comparison of the measured intensities to multislice simulations of diffracted beam intensities allow determination of the order parameter of the particle.FePt films were prepared by co-sputtering high purity Fe and Pt targets onto SiO2/Si substrates using ultra h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…New progresses have been also extensively done in convergent beam electron diffraction (CBED) for nano-sized materials. Normal CBED patterns of volumetric materials show dynamic contrast within the bright discs, as well as diffuse Kikuchi bands and sharp HOLZ lines, but the CBED patterns of nanoparticles only show bright kinematical discs [8]. In addition to this, Tehuacanero-Cuapa et al [14], trying to obtain CBED patterns in Au decahedral nanoparticles of less than 30 nm in size, found that the electron beam perforated the Au nanoparticles, thus concluding that the CBED analysis should be performed with particles larger than 30-nm-in-size to avoid the perforation [14,15].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…New progresses have been also extensively done in convergent beam electron diffraction (CBED) for nano-sized materials. Normal CBED patterns of volumetric materials show dynamic contrast within the bright discs, as well as diffuse Kikuchi bands and sharp HOLZ lines, but the CBED patterns of nanoparticles only show bright kinematical discs [8]. In addition to this, Tehuacanero-Cuapa et al [14], trying to obtain CBED patterns in Au decahedral nanoparticles of less than 30 nm in size, found that the electron beam perforated the Au nanoparticles, thus concluding that the CBED analysis should be performed with particles larger than 30-nm-in-size to avoid the perforation [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Recent advances in transmission electron microscopy (TEM) allow obtaining electron diffraction patterns of nanoparticles as small as 5 nm in size, allowing to study their individual structure [8][9][10]. In many cases, the electron diffraction patterns of nanoparticles show "forbidden" reflections when they are observed by TEM [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the traditional methodology of taking the ratio of the total integrated peak intensities of the superlattice and fundamental reflections according to kinematical scattering theory (Warren, 1990), as done in X-ray diffraction, no longer applies, and S determination becomes more complex. Simulations of electron transmission in crystalline specimens including dynamical scattering are necessary to determine S (Petrova et al, 2005 a , 2005 b ). Figure 1 demonstrates the difficulty of predicting S for [001] and [111] directions in FePt using transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%